IMPACT OF LIFESTYLE FACTORS ON CARDIOVASCULAR RISK IN PATIENTS WITH TYPE 2 DIABETES - Barakayeva Nigina O’tkir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article examines the role of lifestyle factors in modulating cardiovascular risk in patients with type 2 diabetes (T2DM). Diet, physical activity, smoking, alcohol consumption, and stress management significantly influence the development and progression of cardiovascular disease (CVD) in diabetic individuals. Understanding these modifiable factors allows for targeted interventions that can reduce cardiovascular morbidity and mortality and improve overall health outcomes.